Preliminary tax status in local authorities using Geographic Information System (GIS) / Suziana Warde@Warge, Munirah Radin Mokhtar and Nor Eeda Ali - Warde@Warge, Suziana; Mokhtar, Munirah Radin; Ali, Nor Eeda (2022)
This paper represents a preliminary write-up identify the preliminary of monitoring tax payments as a significant agenda to identify the status of household payments and the amount of income for the month for local authorities. This research method combines fieldwork and spatial data processing. The non-spatial database can be integrated with the spatial database to display the area requested by the users. It can be mapped digitally and analysed through a Geographic Information System (GIS). Preliminary studies show how the coordinate data of each home is observed in the field before being processed in the office. The accuracy of spatial data is a very important element to ensure that the resulting data is accurate and precise. At the end of this research, status payment tax can be monitor daily by utilising a web application. As a result, the analysis will help the user plan and take actions in the near future to address the issue.